ANALISIS STRATEGI KORPORAT PENGETAHUAN ASET DAN OPINI PAKAR TERHADAP KINERJA PERUSAHAAN TERBUKA - Yuliana, Lingga; WS, Antonius; Purwoko, Bambang (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2016)
The company's performance has been achieved because of the buying and selling activities in the two markets, namely the consumer market and capital markets. In the capital market activities, the company provides stock and bonds and obtain results in the form of earnings per share. This study will analyze the performance of companies based on the value of Price Eaning Ratio and Price to Book Value Ratio. The purpose of this study is to analyze the corporate strategy in the company's performance. This research uses descriptive quantitative approach. This study applies the strategy through the selection of analysis tools that Analytic Network Process (ANP). The results of this study indicate that intensive strategy is best used for the corporate strategy of the firms as engaged in the cement industry. Intensive best strategy is market penetration strategy then market development strategy and product development with the Analytic Network Process (ANP).